Słoma (dla zwierząt). Subiekcje etymologiczne - Bogalecki, Piotr (Zoophilologica. Polish Journal of Animal Studies, 2017)
The article is an attempt to utilize the pre-philosophical etymological meanings of the word subject in a proposal for the reflection that fits into the discussion on the possibilities of new posthumanistic approaches to the matter of subject. Its first part comprises etymological inquiry, inspired by the philosophy of M. Heidegger and the proposal of K. Okopien, into the Greek word ὑποκείμενον, the Latin subiectum and the Polish podmiot. In the second part, three new, ethically oriented proposals for perceiving the problem in the perspective of studying animals have been derived from the three former meanings of the Polish subject – a foundling, fraud, and bedding.